Should Kenya repeal its domestic limitation of benefits rule in favour of the simplified limitation of benefits rule in the MLI? - Mulama, Doreen Muteyitsi (Department of Commercial Law, 2026)
The Limitation of Benefits (LoB) rule is a recommended measure to fight treaty abuse by the Organization for Economic Cooperation and Development (OECD). It works by preventing residents of third-party states from accessing treaty benefits between states where they do not have sufficient connection in the contracting state based on set criteria. The rule originates from US tax treaty practices and has since been embraced in domestic and treaty practice by other countries worldwide. Kenya is one of the countries that have a domestic LoB rule, which was enacted in 2014. In addition to the domestic LoB rule, Kenya has also elected to include in its treaty practice a version of the rule known as the simplified LoB (SLoB). This has been done under the auspices of the OECD's multilateral tax treaty (MLI). While the two rules operate in different legal realms, there are similarities and differences in their construction and application. Similary, there are different challenges and opportunities in applying each rule in its own legal realm. By analyzing the current law in Kenya, the study highlights the history of the rule and examines its utility for anti-abuse purposes in Kenya today. The SLoB, which is poised to be applied at the treaty level once Kenya ratifies the MLI, is also discussed in detail in contrast to the domestic law provision. The study finds that while the two rules can co-exist, there is a convincing case for why the domestic LOB rule should be repealed. This is because of the main challenge it poses in jurisdictions where it is use which is allowing domestic law to override treaty law. Its repeal will also be a step towards bringing the practice in this area on par with best practices, as reflected in the drafting and content of the treaty version of the rule espoused by the SLoB. The study concludes that for Kenya and other developing countries that have the rule in their domestic law, the MLI presents an opportunity to align with international best practices.